A case study: progressive recurrent course of a giant condyloma (Buschke - Lowenstein tumor) - V. A. Okhlopkov; M. V. Naboka; V. K. Kosenok; V. A. Vodolazsky; YU. A. Novikov; G. N. Ivasyuk; S. B. Glatko (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The authors describe two clinical cases of a malignant giant condyloma (Buschke - Lowenstein tumor), one of which resulted in a lethal outcome. Despite its benign histology, this neoplasm demonstrates evident aggressive and malignant clinical characteristics. The development of this tumor is associated with the papilloma viral infection. Immunodeficiency was diagnosed in the patients in both cases. The lethal outcome was a result of severe anemia, intoxication and local complications. Surgery was the main method of treatment. However, the results were unsatisfactory in view of a weak response to treatment and high risk of relapses. Administration of up-to-date topical immunopotentiators such as Imiquimod seems to be promising because in addition to its principal immunopotentiating effect it may also have a haemostatic action.